Osteoarticular cells tolerate short-term exposure to nitisinone—implications in alkaptonuria. Issue 2 (February 2016) - Mistry, J.; Jackson, D.; Bukhari, M.; Taylor, A.
Abstract Alkaptonuria (AKU) is a rare genetic disease resulting in severe, rapidly progressing, early onset multi-joint osteoarthropathy. A potential therapy, nitisinone, is being trialled that reduces the causative agent; homogentisic acid (HGA) and in a murine model has shown to prevent ochronosis. Little is currently known about the effect nitisinone has on osteoarticular cells; these cells suffer most from the presence of HGA and its polymeric derivatives. This led us to investigate nitisinone's effect on chondrocytes and osteoblast-like cells in an in vitro model. Human C20/A4 immortalized chondrocytes, and osteosarcoma cells MG63 cultured in DMEM, as previously described. Confluent cells were then plated into 24-well plates at 4 × 104 cells per well in varying concentrations of nitisinone. Cells were cultured for 7 days with medium changes every third day. Trypan blue assay was used to determine viability and the effect of nitisinone concentration on cells. Statistical analysis was performed using analysis of variance, and differences between groups were determined by Newman-Keuls post-test. Analysis of C20/A4 chondrocyte and MG63 osteoblast-like cell viability when cultured in different concentrations of nitisinone demonstrates that there is no statistically significant difference in cell viability compared to control cultures. There is currently no literature surrounding the use of nitisinone in human in vitro models, or its effect on chondrocytes or osteoblast like cells. Our results show that nitisinone does not appear detrimental to cell viability of chondrocytes or osteoblast-like cells, which adds to the evidence that this therapy could be useful in treating AKU.